2018
DOI: 10.1111/jocd.12474
|View full text |Cite
|
Sign up to set email alerts
|

Application of lipidomics to reveal differences in facial skin surface lipids between males and females

Abstract: There are significant differences in facial SSL between 18- to 25-year-old males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 9 publications
0
36
2
Order By: Relevance
“…In addition, the TEWL values of the SS group were relatively low yet the water content was relative high, which were inconsistent with the results of previous studies on SS barrier function . It was speculated that this inconsistency might be related to the experimental conditions and the waiting time after face washing.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In addition, the TEWL values of the SS group were relatively low yet the water content was relative high, which were inconsistent with the results of previous studies on SS barrier function . It was speculated that this inconsistency might be related to the experimental conditions and the waiting time after face washing.…”
Section: Discussioncontrasting
confidence: 79%
“…Therefore, this study subsequently tested the sebum composition of the SS and NS groups to further analyse the characteristics of the skin barrier in SS. In addition, the TEWL values of the SS group were relatively low yet the water content was relative high, which were inconsistent with the results of previous studies on SS barrier function [9][10][11]. It was speculated that this inconsistency might be related to the experimental conditions and the waiting time after face washing.…”
Section: Basic Indicatorscontrasting
confidence: 75%
“…[5] We speculated that the reason for the paradoxical occurrence of disparate TEWL and slightly different pH with almost the same circadian rhythm of SSL excretion content would be alterations in SSL composition. In this study, lipidomics and established methods from our earlier studies [8][9][10][11][12][13] were used to reveal the variations in the SSL profile through a comprehensive analysis in order to understand the paradox of dramatically different TEWL and decreased pH with almost the same circadian rhythm of SSL excretion content.…”
Section: Questions Addressedmentioning
confidence: 99%
“…In our earlier studies, the application of this set of methods was used to investigate the alterations in SSL composition in sensitive skin and normal skin, 21 and the different SSL compositions of the skin of men and women. 22 The results showed that there were obvious variations of SSL composition in both sensitive skin and normal skin and in the skin of men and women. Based on our results and the advancements made in studies of skin lipids, the composition of SSL and the relationship between SSL and sensitive skin has been reviewed.…”
mentioning
confidence: 96%
“…We have established a set of methods of sample collection, lipid extraction, data acquisition and analysis based on UPLC‐QTOF‐MS. In our earlier studies, the application of this set of methods was used to investigate the alterations in SSL composition in sensitive skin and normal skin, and the different SSL compositions of the skin of men and women . The results showed that there were obvious variations of SSL composition in both sensitive skin and normal skin and in the skin of men and women.…”
mentioning
confidence: 99%